Trends in OECD Countries' International Competitiveness The Influence of Emerging Market Economies - Durand, Martine (OECD Publishing, 1998)
The large exchange rate depreciations registered in a number of Asian countries since mid-1997 have raised the issue of whether this could lead to major shifts in the relative costs and prices of production across countries, and hence in the relative competitive positions of OECD and non-OECD countries. To take account of the growing importance of Asian emerging economies in world markets, they have been added, together with a number of other non-OECD emerging market economies, to the group of countries covered in the calculation of the OECD Secretariat competitiveness indicators. The main findings that emerge from the analysis presented in this Working Paper are the following: first, the United States is by far the most competitive economy among major OECD countries, both in terms of higher productivity performance and lower absolute cost levels in the manufacturing sector. However, emerging market economies for which data are available display significantly lower levels of unit ...
Keywords: Economics